2016
DOI: 10.3329/brj.v19i2.28167
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance Evaluation of Push Type Prilled Urea Applicator in Rice Cultivation

Abstract: BRRI prilled urea applicator was designed and developed to facilitate deep placement of regular urea. Experiments were conducted to evaluate the performance of BRRI prilled urea applicator in the farmers' fields at Gosaidanga in Shailkupa upazila under Jhenaidah district and at Rashidpur in Mithapukur upazila under Rangpur district during Boro 2015 season. Three treatments: hand broadcasting of urea (recommended dose) (HB), BRRI prilled urea applicator (70% of the recommended dose) (PUA) and BRRI USG applicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…But comparatively higher TGW was observed in USG deep placement (22.48 g) than PU deep placement (21.99 g) method (Table 2). Islam et al, (2015) also found similar results where insignificant effect of urea applicator was on panicle intensity, panicle length and 1000-grain mass. The grain yield of the N-control plot was only 3.05 t ha -1 and with receiving N from different sources and methods the grain yield increased significantly in all treatments over N-control (Table 2).…”
Section: Grain and Straw Yieldsupporting
confidence: 67%
See 1 more Smart Citation
“…But comparatively higher TGW was observed in USG deep placement (22.48 g) than PU deep placement (21.99 g) method (Table 2). Islam et al, (2015) also found similar results where insignificant effect of urea applicator was on panicle intensity, panicle length and 1000-grain mass. The grain yield of the N-control plot was only 3.05 t ha -1 and with receiving N from different sources and methods the grain yield increased significantly in all treatments over N-control (Table 2).…”
Section: Grain and Straw Yieldsupporting
confidence: 67%
“…Actually, all the N treatments produced statistically similar grain yield in Boro season. Islam et al, (2015) found that PU and USG applicators saved 29-32% of prilled urea without sacrificing grain yield in view of the nitrogen management options. Field trials conducted in farmers' fields across different agro-ecological zones (AEZ) showed that UDP with 25-35% less urea produced up to 20% higher yield compared to broadcast PU (Miah et al, 2015;Gregory et al 2010;IFDC 2013) which was dissimilar to this finding.…”
Section: Grain and Straw Yieldmentioning
confidence: 99%
“…The lack of adequate mechanisation has hampered efforts to improve fertiliser placement methods, especially in developing countries. New application devices are required for precise application of fertiliser close to the crop root zone, a procedure that will considerably reduce nutrient loss and maintain fertilisers in the soil (Fujii et al 2015;Islam et al 2016;Yao et al 2018). Furthermore, reductions in nutrient losses that result from local application may reduce the frequency of fertiliser dressing for high-yield crops (Jiang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum increase of organic matter was recorded in Calothrix Mf inoculation. Islam et al (1993) observed that the growth of cyanobacteria in soil can increase organic matter in soil up to 840 kg ha -1 . Our result is in good agreement with the present finding.…”
Section: Organic Mattermentioning
confidence: 99%